2021
DOI: 10.1186/s12931-021-01762-4
|View full text |Cite
|
Sign up to set email alerts
|

Lung macrophages drive mucus production and steroid-resistant inflammation in chronic bronchitis

Abstract: Background Patients with chronic obstructive pulmonary disease (COPD) frequently suffer from chronic bronchitis (CB) and display steroid-resistant inflammation with increased sputum neutrophils and macrophages. Recently, a causal link between mucus hyper-concentration and disease progression of CB has been suggested. Methods In this study, we have evaluated the steroid sensitivity of purified, patient-derived sputum and alveolar macrophages and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Corticosteroid resistance is common in patients with COPD, and several studies have shown that both resident cells in lung (alveolar macrophages) and circulating cells (peripheral-blood mononuclear cells) in patients with COPD are not sensitive to corticosteroid. 25 , 26 In this study, we have explored the role of monocytes/macrophages in corticosteroid insensitivity using COPD PBMCs, CSE-exposed human U937 monocytic cells and confirmed the effectiveness of cryptotanshinone in regaining corticosteroid sensitivity in COPD accompanied by inhibiting PI3K/Akt activity and restoring HDAC2 levels in mononuclear cells. This is the first report to show corticosteroid re-sensitizing capability of cryptotanshinone in modulating PI3K/Akt activity and HDAC2 in the context of COPD.…”
Section: Discussionmentioning
confidence: 52%
“…Corticosteroid resistance is common in patients with COPD, and several studies have shown that both resident cells in lung (alveolar macrophages) and circulating cells (peripheral-blood mononuclear cells) in patients with COPD are not sensitive to corticosteroid. 25 , 26 In this study, we have explored the role of monocytes/macrophages in corticosteroid insensitivity using COPD PBMCs, CSE-exposed human U937 monocytic cells and confirmed the effectiveness of cryptotanshinone in regaining corticosteroid sensitivity in COPD accompanied by inhibiting PI3K/Akt activity and restoring HDAC2 levels in mononuclear cells. This is the first report to show corticosteroid re-sensitizing capability of cryptotanshinone in modulating PI3K/Akt activity and HDAC2 in the context of COPD.…”
Section: Discussionmentioning
confidence: 52%
“…Increased mucus secretion, mucin expression, and inflammatory response in the lungs are indicators of the severity of CB ( Andelid et al, 2021 ). Figure 1C shows that the acidic mucus (red arrow) in the lung tissues of the MC group increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we should determine whether our findings also exist in pulmonary macrophages and airway epithelial cells. Although PBMC and U937 cells are classical vitro models for studying corticosteroid resistance (41), pulmonary macrophages and airway epithelial cells have irreplaceable physiological characteristics (42,43).…”
Section: Discussionmentioning
confidence: 99%